A new single-stage single-switch isolated AC-DC PFC topology with high duty cycle and low current stress and high efficiency - Bodur, Haci; Akboy, Erdem; Yesilyurt, Huseyin; Gundogan, Abdulkerim; Dudak, Ahmet Talha (SPRINGER, 2022)
In this paper, a new single-stage high power factor (PF) isolated AC-DC topology is proposed. In this topology, two DC-DC converters are used, one as a power factor correction (PFC) cell and the other as a regulation (REG) cell. Also, two storage capacitors (SC) are used, one at the input for REG and the other in serial to output for direct power transfer (DPT). PFC cell transfers most power directly to outlet SC with flyback operation and the rest of the power to inlet SC with the simultaneous buck-boost operation. It also provides high PF with discontinuous current mode (DCM). REG cell is fed from inlet SC at low power, works as a power amplifier with DCM, transfers all power to the output provides a tight REG. The topology also provides a high duty cycle (D). Thus, low current stress and high efficiency are achieved with high D and high DPT. The steady-state analysis of the new topology is presented. This analysis is verified by a prototype with output voltage 120 V, output power 120 W, and switching frequency 100 kHz, in 85 V-RMS-265 V-RMS line voltage range. Finally, 51% maximum D, 96% DPT, and 94% efficiency are achieved.
Keywords: Direct power transfer; Low current stress; Power factor correction; Single switch; Single stage; HIGH-POWER-FACTOR; OUTPUT-VOLTAGE; CONVERTER; CELL; BUS; Engineering